The possible implications of Exempt Resolution No. 2076 on the roles and functions of Chilean Counselors (Costa Rican Journal of Guidance & Counseling, 2023)
This article aims to present a comparative analysis between the latest ministerial guidelines of the last thirty years in Chile, in relation to their implications in the roles and functions of Chilean counselors, in addition to understanding the aspects that should be considered for an adequate application in the different educational communities, which leads to strengthen curricularly and operationally the work of the counselors.
Keywords: regulations; educational guidance in Chile; valuing; roles and functions in guidance